2010
DOI: 10.1002/jmri.22139
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic resonance imaging in the evaluation of (deep infiltrating) endometriosis: The value of diffusion‐weighted imaging

Abstract: Purpose: To assess the value of magnetic resonance (MR) diffusion-weighted imaging (DWI) in the evaluation of deep infiltrating endometriosis (DIE). Materials and Methods:In a prospective single-center study, DWI was added to the standard MRI protocol in 56 consecutive patients with known or suspected endometriosis. Endometriotic lesions as well as (functional) ovarian cysts were analyzed for location, size, and signal intensity on T1, T2, and DWI. Apparent diffusion coefficient (ADC) values were calculated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 30 publications
1
32
0
5
Order By: Relevance
“…The signal intensity characteristics of endometrioma on conventional MR sequences as high signal intensity on T1-weighted and T2 shading are usually sufficient for the diagnosis, with specificity greater than 90% (Togashi et al, 1991;Siegelman and Oliver, 2012). Based on the results of a study by Busard et al, endometriomas demonstrate restricted diffusion and low ADC values (Busard et al, 2010). In the present study, initially, endometriomas were not excluded, because we wanted the results be applicable to all of the cases encountered in the clinic.…”
Section: 3407 Differentiation Of Benign From Malignant Adnexal Massementioning
confidence: 94%
“…The signal intensity characteristics of endometrioma on conventional MR sequences as high signal intensity on T1-weighted and T2 shading are usually sufficient for the diagnosis, with specificity greater than 90% (Togashi et al, 1991;Siegelman and Oliver, 2012). Based on the results of a study by Busard et al, endometriomas demonstrate restricted diffusion and low ADC values (Busard et al, 2010). In the present study, initially, endometriomas were not excluded, because we wanted the results be applicable to all of the cases encountered in the clinic.…”
Section: 3407 Differentiation Of Benign From Malignant Adnexal Massementioning
confidence: 94%
“…По данным А. М. Хачатрян и соавт., УЗИ оказа-лось информативным лишь у 4 из 14 больных [5], при этом распознать этиологию узла (эндометриоз или рак) не представлялось возможным. МРТ -зна-чительно более информативный метод диагностики эндометриоза МП [34][35][36][37][38]. Информативность МРТ при эндометриозе МП, по данным А. М. Хачатрян и соавт., составила 82 %, в том числе у 6 больных уда-лось диагностировать эндометриоидные инфильтраты в пузырной стенке (при размере их свыше 1 см) [5].…”
Section: анализ данных литературы и обсуждениеunclassified
“…Информативность МРТ при эндометриозе МП, по данным А. М. Хачатрян и соавт., составила 82 %, в том числе у 6 больных уда-лось диагностировать эндометриоидные инфильтраты в пузырной стенке (при размере их свыше 1 см) [5]. По мнению ряда авторов, для ранней диагностики во-влеченности в процесс мочевых путей, необходимо всем больным генитальным эндометриозом включать в план исследования МРТ малого таза [5,35]. Хорошо выявляя опухолевидные инфильтраты в стенке МП, МРТ, тем не менее, не позволяет надежно дифферен-цировать природу этого образования (эндометриоз или рак) [34,35,38].…”
Section: анализ данных литературы и обсуждениеunclassified
See 1 more Smart Citation
“…No significant difference was found in the mean and lowest ADC values of malignant and benign lesions, and it was concluded that DWI of ovarian lesions and the ADC values of the solid components are not useful for differentiating benign from malignant ovarian lesions. The reported ADC values in malignant ovarian tumors ranged between 0.88×10 −3 mm 2 /s and 2.28×10 −3 mm 2 /s (135)(136)(137)(138)(139)(140)(141). This variability in ADC values is probably due to tumor type, imaging parameters, b value combination, and region of interest placement (whether or not the solid part was included).…”
Section: Female Pelvis Applicationsmentioning
confidence: 99%